(untitled) (Annals of Medical Research, 2021)
Aim: Pancreaticoduodenectomy is a challenging procedure used primarily for the treatment of pancreatic head cancers. The aim of this study was to share early outcomes of the first pancreaticoduodenectomy operations performed by our surgery team after completing a gastroenterological surgery and surgical oncology fellowship program. Material and Methods: Patients who underwent pancreaticoduodenectomy by the same surgical team between November 2015 and August 2018 were retrospectively analyzed. The patients’ demographic data, diagnoses, tumor characteristics, postoperative complications, mortality, and clinical findings during follow-up were recorded. Results: A total of 35 patients (21 men and 14 women) with a mean age of 65.6±18.1 years were included in the study. Mean length of hospital stay was 16.8±7.3 days. Postoperative pancreatic fistula was observed in 5 patients. Postoperative hemorrhage occurred in 3 patients and delayed gastric emptying (DGE) in 2 patients. Three patients died in the early postoperative period. Mean follow-up time of the remaining 32 patients was 22.9±8.4 months. Conclusion: Our experience demonstrates that pancreaticoduodenectomy can be performed with acceptable outcomes after fellowship training that includes pancreatic surgery.Keywords: Whipple; pancreaticoduodenectomy; initial experience.